Judicial Discretion in Sentencing: A Justice System that is No Longer Just? - Mallett, Sean J (Victoria University of Wellington Law Review, 2015)
One of the fundamental principles of the criminal law is consistency: like offenders must be treated alike. However, research has shown that when it comes to sentencing in New Zealand, there is in fact substantial regional disparity in the penalty imposed on similarly situated offenders. The situation is unacceptable, and undermines the integrity of the criminal justice system. This article will explore three different mechanisms for guiding judicial discretion in the pursuit of sentencing consistency. It will undertake an analysis of mandatory sentences and the "instinctive synthesis" approach, both of which will be shown to be unsatisfactory. Instead, the article will argue that the establishment of a Sentencing Council with a mandate to draft presumptively binding guidelines is the most appropriate way forward for New Zealand. This option finds the correct equilibrium between giving a judge sufficient discretion to tailor a sentence that is appropriate in the circumstances of the individual case, yet limiting discretion enough to achieve consistency between cases.